The Design of Visual Identity and Corporate Identity Faraz Cashews in Padang - Ade Moussadecq; Abdi Darmawan; Yan Aditiya Pratama (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2022)
Nowadays, the competition among MSMEs is getting tighter. MSMEs in Padang are competing and building a public image so that their brands and products are known by the public. In Padang, Ulak Karang, there is MSMEs with the Faraz brand. It produces snacks, namely cashew nuts. Faraz MSMEs was founded on February 5, 2006, at the beginning the owner did not have a creative idea to have a visual identity for his business. As a graphic expression, visual identity influences the company's development in the future. Visual identity also acts as a promotional tool for a company/business. The research method uses a qualitative approach method. In this approach, there are 2 sources of data, namely primary data and secondary data. The design of the visual identity of the Faraz brand uses the creative mind mapping method, which is a very common method for finding new ideas, which is based on spontaneity and creativity.